Afghan Women After Talibanization - S. Sumitra; Mohammad Ramin Hakimy; Basel Abou Rokba (PT FORMOSA CENDEKIA GLOBAL, 2023)
Bread, Work, and Freedom nowadays Afghan women slogans in streets of the Kabul capital of Afghanistan who is suffering from fundamentalism prison of Taliban. It is the voice of those who cry out for the depth of their helplessness, suffering, and loneliness under the rule of the Taliban. While screaming these slogans they have to tolerate the insult, humiliation, and mayhem of Taliban forces. With the rise of the Taliban, the demands, rights, and freedoms of Afghan women were limited to the Taliban's Shari'a and their interpretation of Islam. After nearly four months of Taliban rule, have brought nothing but poverty, hunger, unemployment, deprivation, and suffering to women. Moreover, in the darkest day and most symbolic activity after the Taliban took control of Kabul, the Ministry of Women's Affairs' door was closed by the Taliban, and the ministry was renamed